SWOT Analysis of ChatGPT: Implications for Educational Practice and Research - Mesiono, Mesiono; Fahada, Nazli; Irwansyah, Irwansyah; Diana, Diana; Siregar, Andi Suhendra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Technology plays a significant role in our lives today. OpenAI, a company at the forefront of artificial intelligence since 2015, has taken remarkable steps to make artificial intelligence more accessible and beneficial for everyone. One significant achievement in its journey is the development of Chat Generative Pre-trained Transformers (ChatGPT). We used the SWOT analysis framework to outline ChatGPT’s strengths and weaknesses and to discuss its opportunities for and threats to education.  The strengths include using a sophisticated natural language model to generate plausible answers, self-improving capability, and providing personalised and real-time responses. As such, ChatGPT can increase access to information, facilitate personalised and complex learning, and decrease teaching workload, thereby making key processes and tasks more efficient. The weaknesses are a lack of deep understanding, difficulty in evaluating the quality of responses, a risk of bias and discrimination, and a lack of higher-order thinking skills. Threats to education include a lack of understanding of the context, threatening academic integrity, perpetuating discrimination in education, democratising plagiarism, and declining high-order cognitive skills.